2002
DOI: 10.1080/08897070209511485
|View full text |Cite
|
Sign up to set email alerts
|

The Health–Related Effects of Alcohol Use in Older Persons: A Systematic Review

Abstract: Increased alcohol consumption is associated with substantial morbidity and mortality in young and middle-aged adult populations, but its effects on the health of older adults have received less attention. The objective of the study was to review published studies that assessed the effects of alcohol on falls or fall injuries, functional impairment, cognitive impairment, and all-cause mortality among older adults. MEDLINE database and bibliographies of selected citations were searched for English language studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 107 publications
4
58
0
1
Order By: Relevance
“…In our study, ex-drinkers had an increased mortality risk compared to moderate drinkers, consistent with other studies (Holahan et al 2010). In contrast to a systematic review (Reid et al 2002), heavy alcohol consumption was not a significant risk factor for mortality in our study. These conflicting findings may be due to lack of standardisation in the classification of moderate and heavy drinking, cultural differences in drinking habits and measurement error in self-reports of alcohol consumption.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, ex-drinkers had an increased mortality risk compared to moderate drinkers, consistent with other studies (Holahan et al 2010). In contrast to a systematic review (Reid et al 2002), heavy alcohol consumption was not a significant risk factor for mortality in our study. These conflicting findings may be due to lack of standardisation in the classification of moderate and heavy drinking, cultural differences in drinking habits and measurement error in self-reports of alcohol consumption.…”
Section: Discussionsupporting
confidence: 90%
“…The Connecticut Veterans Longitudinal Cohort was a prospective cohort of patients at the Veterans Administration (VA) Healthcare System in West Haven, Connecticut. 15 The cohort enrolled a consecutive series of veterans attending VA primary care clinics from July 2000-August 2001. Inclusion criteria were age 65 years or older, English speaking, ability to ambulate independently within the clinic either with or without an assistive device, and ability to give informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…In their systematic review of the health-related effects of alcohol use in older persons, Reid et al [32] found four studies in which an average weekly consumption of either ≥ 10 drinks per week (alcohol content of drink varied across countries and not defined), a history of heavy use, or an increasing number of drinks consumed per occasion were associated with greater risk for functional disability when compared with non-drinkers or participants with no history of heavy drinking. One additional study found that ≥ 14 drinks per week increased risk for functional disability among men, but not women.…”
Section: Alcohol and Well-beingmentioning
confidence: 99%